Maize-grain legume intercropping for enhanced resource use efficiency and crop productivity in the Guinea savanna of northern Ghana - Kermah Michael; Franke Angelinus C.; Adjei-Nsiah Samuel; Ahiabor Benjamin D.K; Abaidoo R. C; Giller Ken E. (Elsevier, 2023)
This article is Published by Elsevier, 2018 and is also available at http://dx.doi.org/10.1016/j.fcr.2017.07.008